Determination of the real relationship between symphyseal morphology and different growth patterns among orthodontic patients of Maharajgunj medical campus, dental teaching hospital. - Gosain,Nabin (2020)
ABSTRACT: Introduction: The symphysis is one of the most important region of the craniofacial complex. It serves as a primary reference for esthetic considerations in the lower one-third of the face. In orthodontics, knowledge of mandibular growth is highly beneficial in diagnosis and treatment planning and is critical in the development of balanced dentofacial structures. The size of the symphysis represents a biological and biomechanical limit to the position of the lower incisors. The present study focuses on cephalometric analysis of the symphyseal morphology and relationship with different growth patterns. Objectives: To determine the relationship between symphyseal morphology and different growth pattern among orthodontic patients. Materials and Methods: Pre-treatment lateral cephalograms of 105 orthodontic patients visiting Department of Orthodontics and Dentofacial Orthopedics were taken and equally divided into three group of 35 samples in each as Group I (normal growth pattern), Group II (horizontal growth pattern) and Group III (vertical growth pattern). Mean and standard deviation of symphyseal height, symphyseal width, symphyseal ratio and symphyseal angle for all the groups were measured from lateral cephalograms. ANOVA test was used to calculate difference between groups and within groups for all measurements. Pearson correlation coefficient was calculated to determine correlation between mandibular growth pattern, symphyseal ratio and symphyseal angle. Differences in symphyseal height, symphyseal width, symphyseal ratio and symphyseal angle between male and female samples were tested using ANOVA. Results: The lateral cephalograms of total 105 patients (Female=52 and Male=53) met the inclusion criteria with mean age of the samples 21.43 years (SD=3.19). The mean values for the symphyseal height were greatest for the vertical growth pattern (22.314 mm ± 1.94), followed by the horizontal growth pattern (20.614 mm ± 1.43) and then the normal growth pattern (20.371 mm ± 2.31). There were significant differences between normal and vertical growth pattern; horizontal and vertical growth patterns. The mean values for the symphysis width were greatest for the horizontal growth pattern (14.957 mm ± 1.14) followed by normal growth pattern (14.043 mm ± 1.43) and then the vertical growth pattern (13.145 mm ± 1.45) which were found statistically significant difference among three groups. The mean values for symphyseal ratio were greatest for the vertical growth pattern (1.707 ± 0.09), followed by the normal growth pattern (1.448 ± 0.15) and then the horizontal growth pattern (1.38± 0.04) which showed significant difference among the three groups. For symphyseal angle, there was only statistically significant results between vertical (76.93 ± 4.21º) and horizontal (80.20 ± 5.43º) growth patterns. There was correlation found between different growth pattern and symphyseal parameters. There were increased measurements of symphyseal height and symphyseal width in all growth patterns in males than in females. Conclusions: The symphysis with the vertical growth pattern had a large height, small depth, large ratio, and small angle in comparison to horizontal and normal growth pattern. In contrast, a symphysis with a horizontal growth pattern had a small height, large depth, small ratio, and large angle. Sexual dimorphism was found with mean symphysis height and depth in the female sample being smaller than in the male sample. Key Words: Mandibular Symphysis, Symphyseal morphology, Craniofacial growth pattern, Cephalometric analysis